Determinants of Impulsive Buying Among Students: Implications for Responsible Consumption and Sustainable Development - Handini Retnowati; Arina Salsabilla Haq (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
behavior among university students, focusing on low self-control, social networking impulsivity, and positive attitudes toward targeted advertising in Generation Z students in Indonesia. Method: The approach used is nvolving simple random sampling of 174 students from the Education Program at the Faculty of Economics and Business, Universitas Negeri Surabaya. Data were collected using a five-point Likert scale questionnaire, adapted from prior studies, and analyzed through Structural Equation Modeling (SEM-PLS) to assess direct and mediating effects. Results: The findings indicate that low self-control significantly affects impulsive buying both directly and indirectly through social networking impulsivity. While low self-control also influences positive attitudes toward targeted advertising, these attitudes do not mediate impulsive buying. Furthermore, social networking impulsivity significantly mediates the relationship between low self-control and impulsive buying, highlighting the dominant role of social media-related impulsivity. Novelty: This study offers an integrated perspective by simultaneously examining low self-control, social networking impulsivity, and attitudes toward targeted advertising in Indonesian Gen Z students. It extends the Theory of Planned Behavior (TPB) by demonstrating that, in the digital consumption context, attitudes may not always act as effective mediators, whereas social media-related impulsivity is crucial. The findings provide both theoretical contributions and practical guidance for improving students’ digital economic literacy and managing impulsive buying behavior responsibly.